Esporte no contexto escolar: estudo do perfil dos professores de educação física qua atuam como técnicos nas olimpíadas estudantis no município de São Paulo - Nunes, Hudson Fabricius Peres [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This study aimed to establish relations and comprise if there is consistency between the profile of curriculum graduation and sports conception of the teachers-coaches finalists of the Students Olympics (OE) in the city of São Paulo in relation to Nacional Curriculum Guidelines (DCNs), that guide the College Institutions (IES) to define the profile of formation of the bachelor degree in Physical Education based on Resolutions CNE/CP n. 01 and 02/02, Law of Directives and Bases (LDB), National Curriculum Parameters (PCNs) and the More Education Program, and simultaneously, the relationship between teachers-coaches profile with school sports of promoted income by the OE and Athlete in School Program, according to the regulations of Decree n. 7.984/13. The methodology used is based in qualitative research, being splited into two stages: I) exploratory phase: use of documentary sources and bibliography review; II) descriptive phase: characterization of the profile of curriculum formation and profile description of sports conception of teachers-coaches, using as investigation instrument the almost structured questionnaire and as technique the content analysis. Before the presented objectives, it was established that the studied profile hold curriculum formation predominant in the resolutions CFE n. 69/69 and 03/87, with exception of four participants formed under surveillance of the current DCNs with the baccalaureate degree graduation subsequent to bachelor. The profile of curriculum formation of the teachers-coaches approach to the characteristics of traditional-sports curriculum. In conclusion, the profile of sports graduation and conception predominant of the teachers-coaches of OE is coherent with the objectives of the Ministry of Sport in promoting the school sport, detect talent and shape them sportily through the School Games and Athlete in School Program, according to the regulations of Decree n. 7.984/13, and at the same time, is ...

Este estudo objetivou estabelecer relações e compreender se há coerência entre o perfil de formação curricular e concepção esportiva dos professores-técnicos finalistas das Olimpíadas Estudantis (OE) do município de São Paulo em relação às Diretrizes Curriculares Nacionais (DCNs), que orientam as Instituições de Ensino Superior (IES) a definirem o perfil de formação do curso de licenciatura em Educação Física baseado nas Resoluções CNE/CP n. 01 e 02/02, Lei de Diretrizes e Bases (LDB), Parâmetros Curriculares Nacionais (PCNs) e Programa Mais Educação, e de forma simultânea, a relação entre o perfil dos professorestécnicos com o esporte escolar de rendimento promovido pelas OE e Programa Atleta na Escola, conforme a regulamentação do Decreto n. 7.984/13. A metodologia utilizada fundamenta-se na pesquisa qualitativa, sendo dividida em duas etapas: I) fase exploratória: utilização de fontes documentais e revisão bibliográfica; II) fase descritiva: caracterização do perfil de formação curricular e descrição do perfil da concepção esportiva dos professorestécnicos, utilizando como instrumento de investigação o questionário semiestruturado e como técnica a análise do conteúdo. Diante dos objetivos apresentados, constatou-se que o perfil estudado possui formação curricular predominante das Resoluções CFE n. 69/69 e 03/87, com exceção de quatro participantes formados sob a vigência das atuais DCNs com a formação de bacharelado subsequente à licenciatura. O perfil de formação curricular dos professorestécnicos se aproxima das características do currículo tradicional-esportivo. Conclui-se que o perfil de formação e concepção esportiva predominante dos professores-técnicos das OE está coerente com os objetivos do Ministério do Esporte em promover o esporte escolar, detectar talentos e formá-los esportivamente através dos Jogos Escolares e Programa Atleta na Escola, conforme a...
Keywords: Teachers, Training of; Educação fisica; Professores - Formação; Professores de educação fisica; Esportes escolares; Curriculos; Esportes; São Paulo (SP)